Implementasi Tafsir Tarbawi dalam Proses Pendidikan - Nasution Nasution (STIKes Ibnu Sina Ajibarang, 2026)
Tafsir tarbawi is an approach to interpreting the Qur’an that emphasizes the extraction of educational values to shape holistic human character. This study aims to analyze the implementation of tafsir tarbawi in the process of Islamic education and examine its relevance in shaping students’ character in the modern era. The research employs a qualitative method with a library research approach, where data are collected through the analysis of various academic sources such as books, scholarly journal articles, and relevant previous studies. The findings indicate that tafsir tarbawi can be effectively implemented through the integration of Qur’anic values into educational curricula, the application of value-based learning methods, and the reinforcement of teachers’ exemplary behavior as role models. Furthermore, this approach encourages the internalization of spiritual, moral, and social values within students. Therefore, tafsir tarbawi plays a strategic role in developing learners who are not only intellectually competent but also possess strong character, noble morals, and the ability to face life’s challenges wisely.